Dielectric and piezoelectric properties of 0.7 Pb(Mg1/3Nb2/3)O3-0.3 PbTiO3 single crystal poled using alternating current. Issue 10 (3rd October 2018) - Chang, Wei-Yi; Chung, Ching-Chang; Luo, Chengtao; Kim, Taeyang; Yamashita, Yohachi; Jones, Jacob L.; Jiang, Xiaoning
ABSTRACT: In this paper, 0.7Pb(Mg1/3 Nb2/3 )O3 -0.3PbTiO3 (PMN-30%PT) single crystal samples were poled using an alternating current (electric field) poling (ACP) method. Compared to the traditional poling method, the piezoelectric coefficient, free and clamped dielectric constants were improved more than 21%. X-ray diffraction result suggests the existence of monoclinic phase ( MA ) in ACP samples and piezoresponse force microscopy (PFM) result further depicts the finer engineered domain structures. The ACP sample also showed the unique phase transition sequences during the depoling process. Our work could provide a novel domain engineered method to enhance piezoelectric properties of PMN-PT single crystal. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Piezoelectric and dielectric properties of relaxor-PT single crystals can be significantly enhanced by employing the new alternating current poling method, attributing to the unique heterogenous domain structure containing unprecedented domain wall density.